The Itea-Amfissa detachment: a pre-Corinth rift Miocene extensional structure in central Greece - Papanikolaou, Dimitrios; Gouliotis, Leonidas; Triantaphyllou, Maria (Geological Society, London, Special Publications, 2009)
The Itea-Amfissa valley, separating Giona Mountain to the west from Parnassos Mountain to the east, is related to an extensional detachment observed along the eastern slopes of Giona. The detachment is traced for 30 km north of the Corinth Gulf and dips 25{degrees}-40{degrees} to the east, showing an east-west extension parallel to the Hellenic arc. The lower nappes of Pindos, Penteoria, Vardoussia and mainly the basal thrust of the Parnassos unit form part of the footwall, whereas the upper thrusts of the Parnassos unit and the Western Thessaly-Beotia nappe form part of the hanging wall. The eastern slopes of Giona are controlled by the detachment and several hundred metres of syn-tectonic breccia-conglomerates are observed at the top of the hanging wall rocks and are back-tilt towards the detachment plane. Two conglomeratic sequences are distinguished: the lower one consists of argillaceous matrix and abundant ophiolite detritus whereas the upper one bears carbonate matrix with carbonate detritus together with large olistholites of Mesozoic limestones. Based on calcareous nannofossils a middle Miocene age has been determined for the lower formation and a middle-upper Miocene age is probable for the upper. Planation surfaces cut on top of the sediments rise from south to north starting from sea level at Galaxidi to about 1400 m at Prosilio. The throw of the detachment is about 2.5-4.2 km measured mainly from the structural omission of the Alpine tectono-stratigraphic units. A contrast between the footwall and the hanging wall structure is described, with monoclinic sequence of the Parnassos nappe dipping to the west in the footwall but a complex synsedimentary horst and graben structure of sliding blocks of Alpine formations within the Miocene clastic sequences in the hanging wall. The detachment has been deformed by the east-west-trending steep normal faults that have created the Corinth rift during late Pliocene-Quaternary time showing a north-south extension. The Itea-Amfissa detachment forms the northern tip of the broader East Peloponnesus detachment, observed south of the Corinth rift structure from Feneos to Kyparissi. Similar geodynamic phenomena with large olistholites and breccia conglomerates are known from the Serravalian of Crete, related to the activity of the Cretan detachment.